Analysis of Building Distribution and Conformity with The Spatial Plan of Medan City Case Study: (Land/State Property in Medan Polonia District) - Yahya Naufal Hawari; Abdiyanto; Ihsan Azhari (Yayasan Multidimensi Kreatif, 2024)
This study aims to examine the analysis of the distribution of buildings and their conformity with the spatial plan of the city of Medan. Qualitative research that must be considered is the problem and focus of the research. The focus of this research plays a very important role in guiding and directing the course of a research. Meanwhile, the data reduction obtained in the study was written or typed in the form of a detailed description. The reports are reduced, summarized, selected the main things, focused on important things, sought for themes or patterns, so field reports as raw materials are systematically prepared so that they are easier to control. The results of the research on the Medan City Regional Spatial Pattern Plan are a direction for the use of space in the Medan City area which is based on the principle of utilizing natural resources based on environmental sustainability towards sustainable development. This direction is expected to create growth and development between parts of the Medan City area that are more balanced in proportion, without disturbing the sustainability of the environment. The role of the Regional Government of Medan City in the implementation of spatial planning in the city of Medan is very important in the formulation of technical policies and the implementation of spatial planning in the city of Medan is to prepare a general spatial plan, namely the spatial plan of the city and to prepare a detailed spatial plan, namely the strategic spatial plan of the city. This plan is then outlined in the form of a regional spatial plan (RTRW) which will then be regulated in the form of regional regulations within a certain period of time.